Answer:
![(x + 3)(x - 2)(x - 1)](https://tex.z-dn.net/?f=%28x%20%20%20%20%20%2B%20%203%29%28x%20%20%20-%20%202%29%28x%20-%201%29)
Step-by-step explanation:
![{x}^{3} - 7x + 6](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B3%7D%20%20-%207x%20%2B%206)
Factor using Rational Root Theorem.
This means our possible roots are
positve or negative (1,2,3,6). If we try positve 1, it is indeed a root.
This means that
![(x - 1)](https://tex.z-dn.net/?f=%28x%20-%201%29)
is a root.
We can divide the top equation by the root (x-1). Our new equation is
![( {x}^{2} + x - 6)](https://tex.z-dn.net/?f=%28%20%7Bx%7D%5E%7B2%7D%20%20%20%2B%20%20x%20-%206%29)
Now we can factor this completely
![(x + 3)(x - 2)](https://tex.z-dn.net/?f=%28x%20%2B%203%29%28x%20-%202%29)
So this equation in factored form is
![(x + 3)(x - 2)(x - 1)](https://tex.z-dn.net/?f=%28x%20%20%2B%203%29%28x%20-%202%29%28x%20-%201%29)
The rational bumber between -2 and 0 is -1
Answer:
3/4b−2/3b=−9 = -108. so, i just used equivalent fractions of both of those numbers :D
Step-by-step explanation:
6/8b - 4/6b = -9